Bank Bail-outs, International Linkages and Cooperation - Friederike Niepmann; Tim Schmidt-Eisenlohr (Verein für Socialpolitik, 2010)
Financial institutions are increasingly linked internationally and engaged in cross-border operations. As a result, financial crises and potential bail-outs by governments have important international implications. Extending Allen and Gale (2000), we provide a model of international contagion allowing for bank bail-outs financed by distortionary taxes. In the sequential game between governments, there are inefficiencies due to spillovers, free-riding and limited burden-sharing. When countries are of equal size, an increase in cross-border deposit holdings improves, in general, the non-cooperative outcome. For efficient crisis managment, ex-ante fiscal burden sharing is essential as ex-post contracts between governments do not achieve the same global welfare.
Keywords: F36; G28; F42; 330; bail-out; contagion; financial crisis; international institutional arrangements